Investigation of Azorean macroalgae for angiotensin I-converting enzyme (ACE) inhibitory peptides. Extraction, purification and antihypertensive activity evaluation - Paiva, Lisete S. (2022)
62nd International Congress and Annual Meeting of the Society-of-Medicinal-Plant-and-Natural-Product-Research, AUG 31-SEP 04, 2014, Guimaraes, PORTUGAL.